1962
DOI: 10.1085/jgp.45.5.989
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid-Cholesterol Membrane Model

Abstract: A cephalin-cholesterol membrane model is described whose electrical resistance can be reversibly raised by CaCl2 or lowered by KCl or NaCl whether these ions are added to the membrane by mechanical immersion or are driven in electrically. Either KCl or NaCl acts antagonistically to CaCl2. Experiments with controlled pH indicate that the above effects depend somehow on combination of the cations with the phospholipid acidic groups. Also, they are correlated with decreased membrane hydration in CaCl2 solutions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

1962
1962
1986
1986

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…The results reported here are in agreement with the findings of othe: authors who have studied the interaction of calcium ions, either witt fragments of natural biological membranes [5,20] or with artificial phos pholipid membranes [23][24][25]28]. In both cases, the interaction has beeI shown to be pH dependent.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results reported here are in agreement with the findings of othe: authors who have studied the interaction of calcium ions, either witt fragments of natural biological membranes [5,20] or with artificial phos pholipid membranes [23][24][25]28]. In both cases, the interaction has beeI shown to be pH dependent.…”
Section: Discussionsupporting
confidence: 92%
“…This behavior is rather similar to that of phospholipid monolayers [23][24][25]28]. Some years ago, Straub [27] reported that the depolarization of frog myelinated nerve fiber membrane, caused by calcium deprivation, was increased by alkaline and decreased by acid pH.…”
supporting
confidence: 63%
“…Studies described in this series of papers have been undertaken along this line of thought. A similar attempt was discussed by Tobias, Agin and Pawlowski [10] some years ago.…”
mentioning
confidence: 73%
“…In addition, MacFarlane & Knight (1941) reported that it possesses phospholipase C activity. The toxin can hydrolyze various phospholipids such as phosphatidylcholine in biological membranes (Tobias et al, 1962; Lenard & Singer, 1968;McILwain & Rapport, 1971;Knickelbein & Rosenberg, 1980). Several workers have reported various biological properties of the crude or the partially purified toxin, especially the experimental production of lesions by administration to various tissues of the crude or partially purified alpha toxin preparation (Strunk et al, 1967;Albuquerque & Thesleff, 1967;Lodge & Leach, 1973;Knickelbein & Rosenberg, 1980).…”
Section: Introductionmentioning
confidence: 99%